Synthesis, X-Ray Crystal Structure, Solid State Electrical and Optical Properties of New Copper(II) Complex with 1,10-Phenanthroline Ligand - Sarkar, Saikat; Sarkar, Avijit; Aydogdu, Yildirim; Dagdelen, Fethi; Sarkar, Sougata; Chattopadhyay, Krishna (Asian Publication Corporation, 2024)
A new ionic copper(II) complex of 1,10-phenanthroline was synthesized and structurally characterized by elemental and spectroscopic analyses, molar conductance and magnetic moment measurements. The crystal structure of complex was also investigated through single crystal X-ray diffraction analysis and suggestted a distorted octahedral geometry around copper(II), where one N atom from 1,10-phenanthroline and three O atoms from three H2O molecules occupying the basal plane while another Nphen and one Cl atom remain at the apical positions. Thus, the presence of three coordinated waters and chloride group along with the counter chloride ion and water of crystallization is responsible for extensive hydrogen bonding present in the molecule. Thus, the complex forms a 3D gigantic H-bonded network. The two types of intermolecular O–H···Cl and O–H···O hydrogen bonding play the pivotal role in crystal packing and plausible conductivity mechanism through the ?-? interacting supports. The electrical conductivity and optical properties were also measured and the results focus on the semiconducting nature of the complex with optical band gap (Egd) value 1.23 eV. © 2024 Asian Publication Corporation. All rights reserved.
Keywords: Complex; Crystal structure; Electrical properties; Semiconductor; Spectroscopy